Together, apart : stories - Craig, Erin A.; Desombre, Auriane; Hahn, Erin; Konigsberg, Bill; Lippincott, Rachael; Morris, Brittney; Patel, Sajni, 1981-; Preston, Natasha; Yen, Jennifer (Delacorte Press, an imprint of Random House Children's Books, 2020)
A collection of original contemporary love stories set during life in lockdown by some of today's most popular YA authors.